Perinatal Risks in “Late Motherhood” Defined Based On Parity and Preterm Birth Rate – an Analysis of the German Perinatal Survey (20th Communication) - Schure, V.; Voigt, M.; Schild, R. L.; Hesse, V.; Carstensen, M.; Schneider, K. T. M.; Straube, S. (Geburtshilfe und Frauenheilkunde, 2012)
Aim: “Late motherhood” is associated with greater perinatal risks but the term lacks precise definition. We present an approach to determine what “late motherhood” associated with “high risk” is, based on parity and preterm birth rate. Materials and Methods: Using data from the German Perinatal Survey of 1998–2000 we analysed preterm birth rates in women with zero, one, or two previous live births. We compared groups of “late” mothers (with high preterm birth rates) with “control” groups of younger women (with relatively low preterm birth rates). Data of 208 342 women were analysed. For women with zero (one; two) previous live births, the “control” group included women aged 22–26 (27–31; 29–33) years. Women in the “late motherhood” group were aged > 33 (> 35; > 38) years. Results: The “late motherhood” groups defined in this way were also at higher risk of adverse perinatal events other than preterm birth. For women with zero (one; two) previous live births, normal cephalic presentation occurred in 89 % (92.7 %; 93.3 %) in the “control” group, but only in 84.5 % (90 %; 90.4 %) in the “late motherhood” group. The mode of delivery was spontaneous or at most requiring manual help in 71.3 % (83.4 %; 85.8 %) in the “control” group, but only in 51.4 % (72.2 %; 76.4 %) in the “late motherhood” group. Five-minute APGAR scores were likewise worse for neonates of “late” mothers and the proportion with a birth weight ≤ 2499 g was greater. Conclusion: “Late motherhood” that is associated with greater perinatal risks can be defined based on parity and preterm birth rate.
Keywords: late motherhood; parity; preterm birth rate; perinatal risks; German Perinatal Survey